Evaluating english language proficiency level in reading and listening skills in senior students at “Provincia de Cotopaxi” high school in Pujil - Vergara Espinoza, Johnny Alejandro (2023)
Evaluating English Proficiency in language skills is fundamental for secondary students during their learning process. This mixed-method study aimed to establish the current level of language proficiency of Senior students at “Provincia de Cotopaxi” High School. Specifically, it determined English proficiency in receptive skills; reading, and listening. The subject of this study comprises 40 Senior students selected using probability sampling technique, and two English teachers enrolled in the High School in the academic period 2022 – 2023. The researcher adopted a standardized test from Cambridge: Key English Test (KET) in reading and listening parts. Likewise, it was used a structured interview as an instrument to gather non-numerical data. For the analysis of quantitative data obtained it was used Descriptive Statistics (mean), and for the analysis of qualitative data, the researcher used Thematic analysis in order to make categories and to review the teachers’ perceptions and experiences related to the evaluation applied. The main findings of this study show that students varied their reading and listening English proficiency. Overall results from the statistic mean scores determine that participants are ‘modest users’ or they have a preIntermediate level of reading comprehension. However, the students present a Beginner level or they are ‘basic users’ in listening. It is therefore recommended that English teachers from this High School should integrate extra classes, meaningful activities for the improvement of reading and listening skills.